Penguatan Kapasitas Guru Sekolah Dasar dalam Implementasi Kurikulum Pendidikan Inklusi Berbasis Universal Design for Learning (UDL) - Raihan, Siti; Wizerti Ariastuti; Awayundu Said; Nurul Mutahara B; Amir Pada (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2025)
Inclusive education requires teachers to design and implement learning experiences that are responsive to student diversity; however, studies consistently show that many elementary school teachers still face challenges in applying inclusive approaches effectively. This community engagement program aimed to strengthen the capacity of elementary school teachers in implementing an Inclusive Education Curriculum based on Universal Design for Learning (UDL) through comprehensive training and mentoring. The program was conducted over four months in six inclusive elementary schools in Makassar City, involving 15 teachers, and employed interactive workshops, on-site mentoring, and online consultation and discussion. The results indicate significant improvements in three key areas of teacher competence: understanding of UDL principles, ability to differentiate instruction, and skills in designing inclusive learning materials. Teachers also demonstrated more adaptive, collaborative, and student-centered instructional practices after participating in the program. These findings imply that professional development combining theoretical understanding, practical application, and continuous mentoring effectively enhances teachers’ readiness to consistently implement inclusive curriculum practices. In conclusion, this capacity-building model proved effective in improving teacher professionalism and supporting the creation of inclusive learning environments that are more welcoming, flexible, and accessible for all students.